Effects of tillage methods on physical properties of a clayey yellow Latosol in the state of Amazonas - Corrêa, José Carlos (Pesquisa Agropecuaria Brasileira, 2014)
The effects of tillage systems, conventional, rotary hoe ("rotavator") and non-tillage (direct sowing) on the structure of a clayey Yellow Latosol, originally under primary forest vegetation, was evaluated at the EMBRAPA-UEPAE Experiment Satation at Manaus, Amazonas. Bulk density, macro, micro and total porosity, and aggregate stability in water were influenced by systems in the 0 cm- 10 cm and 10 cm-20 cm soil sampling depths. The 0 cm-10 cm depth in the non-tillage systems, presented the greatest increases in bulk density and, consequently, the largest reductions in macro and total porosity. Aggregate stability in water was only affected in the 0 cm -10 cm depth by the conventional and rotary hoe systems. Correlations between organic matter and mean aggregate diameter were low (r = 0,30) due to the clay content (81%) of this soil.